Synthesis of 17,20α/β-dihydroxy-4-pregnen-3-one and 5β-pregnanes in spermatozoa of primary and 17α-methyltestosterone-induced secondary male grouper (Epinephelus coioides) - Lee, S.T.L. (2014)
10.1006/gcen.1998.7122